1987
DOI: 10.1093/nar/15.19.8041
|View full text |Cite
|
Sign up to set email alerts
|

Gene cluster for streptomycin biosynthesis inStreptomyces griseus: nucleotide sequence of three genes and analysis of transcriptional activity

Abstract: Three streptomycin (SM) production genes from Streptomyces griseus clustered around aphD, the major resistance gene, have been sequenced: strB, coding for an aminocyclitol amidinotransferase, ORF5 (strR), a putative regulatory gene, and ORF1 (strD), possibly coding for a hexose nucleotidylating enzyme. Three promoters and at least five, partially overlapping, transcripts have been identified by S1 mapping and Northern blot experiments. aphD, the resistance gene, is transcribed from two promoters. One of them, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 26 publications
4
91
0
Order By: Relevance
“…Orf4.1 is thus @A and not @C or @D as suggested previously ; the correct identification of @C and @D will be described later. The glucose-l-phosphate thymidylyltransferase of strain LT2 shows 34 % identity to that of Streptomyces greceus (strD of [15]; personal communication, W. Pipersberg). The SDSPAGE estimated subunit mass for rfbA protein of 31 kDa agrees well with the value of 32453 kDa, calculated from the amino acid composition deduced from the nucleotide sequence of the orf6.1 gene.…”
Section: Reaction Directionmentioning
confidence: 99%
“…Orf4.1 is thus @A and not @C or @D as suggested previously ; the correct identification of @C and @D will be described later. The glucose-l-phosphate thymidylyltransferase of strain LT2 shows 34 % identity to that of Streptomyces greceus (strD of [15]; personal communication, W. Pipersberg). The SDSPAGE estimated subunit mass for rfbA protein of 31 kDa agrees well with the value of 32453 kDa, calculated from the amino acid composition deduced from the nucleotide sequence of the orf6.1 gene.…”
Section: Reaction Directionmentioning
confidence: 99%
“…For the first three compounds, it has been reported that their biosynthesis is controlled by the action of specific regulatory genes located within the particular biosynthetic clusters (4,(7)(8)(9). Such regulatory genes have also been identified in other antibiotic clusters, such as bialaphos (10), streptomycin (11,12), and daunorubicin (13).…”
mentioning
confidence: 99%
“…Also, the StrD proteins, which are encoded by both related str/sts gene clusters for the biosynthesis of Sm and OH-Sm in S. griseus and S. glaucescens, respectively, are significantly, but more distantly related proteins. The StrD proteins belong to the subfamily of dTDP-D-glucose synthases and they catalyse the first step in dTDP-L-rhamnose synthesis in both strains (Distler et al, 1987;Verseck, S. and Piepersberg, W., unpublished). However, with StrQ the highest degree of similarity was detected to the subfamily of CDP-glucose synthases which have so far only been described from Enterobacteria, Bacillus subtilis and Synechocystis sp.…”
Section: Similarity Of the Strq Protein To Proteins In The Data Basementioning
confidence: 99%
“…The genes/enzymes for the activation, modification, and transfer of NDP-hexose precursors are still incompletely known. The enzymes encoded by the genes strDELM, encoding a dTDP-D-glucose synthase (StrD), a dTDP-D-glucose 4,6-dehydratase (StrE), a dTDP-4-keto-6-deoxy-D-glucose 3,5-epimerase (StrM), and a dTDP-L-rhamnose synthase (StrL) occur in all (OH-)Sm-producing strains and seem to be involved in the formation of dTDP-L-dihydrostreptose (Distler et al, 1987;Pissowotzki et al, 1991;Verseck, S. and Piepersberg, W., unpublished). The gene for the dTDP-L-dihydrostreptose synthase catalysing the final step has still to be identified.…”
mentioning
confidence: 99%